Practical problems in mathematics for carpenters - Huth, Harry C. (Thomson Delmar Learning, 2006)
This widely used text/workbook teaches the practical mathematics essential the building construction and carpentry trades. The book features short units that begin with a brief explanation of an important math principle followed by straightforward explanations and examples that are worked out in detail so readers can see first-hand how to perform the functions involved. Basic mathematical problems relevant to the construction trade are accompanied by clear-cut illustrations and together give readers the opportunity to apply and practice math principles common to carpentry.